Legal Protection for Wives Regarding Disputed Joint Property Issues in Divorce Lawsuits - Sri Hariati; Musakir Salat; Ita Surayya; Fatahullah Fatahullah (JILPR Journal Indonesia Law and Policy Review, 2023)
The purpose of this counseling is to understand the recognition of disputed joint property in divorce lawsuits and how the system of dividing contested joint property works in divorce lawsuits. It serves as input for readers, academics, and government authorities. The research method used is normative empirical legal research. The filing of joint property lawsuits can be done simultaneously with divorce lawsuits, child custody, child support, and spousal support (consolidated lawsuits) or separately after the divorce lawsuit is finalized. Both the husband and wife can file consolidated lawsuits. The wife can file more lawsuits than the husband, particularly in cases of spousal support (iddah and mut'ah), while if the husband files a lawsuit for spousal support, it becomes problematic because spousal support is the husband's obligation. The wife is entitled to iddah support. The common obstacle in seeking legal protection through joint property lawsuits in divorce cases is the wife's limited legal knowledge, which can affect outcomes that do not meet expectations.